Model Pembelajaran Inseta-Stick Untuk Meningkatkan Minat Belajar Dalam Pembelajaran Pendidikan Kewarganegaraan Pada Siswa Kelas VIII A SMP Negeri 1 Wonosari Kabupaten Klaten Tahun Pelajaran 2015/2016 - Nugroho, Muchlis, Prof. Dr. H. Bambang Sumardjoko, M.Pd (2016)
This study aims to increase interest in learning to use INSETA-STICK learning model that combines strategy Information Search by Talking Stick in Citizenship Education learning in class VIII A of SMP Negeri 1 Wonosari Klaten district in the academic year 2015/2016. Learning interest of the students was very low before the test models and teachers are seeking alternative solutions using varied discussion, question and answer, and Card Sort. The use of these methods was not yet able to increase student interest. The solution in this research is to use INSETA-STICK learning model that combines strategy Information Search by Talking Stick. Subject of research implementation is class VIII A of SMP Negeri 1 Wonosari Klaten district in the academic year 2015/2016, amounting to 32 children. Data collection techniques using observation and interview methods. The procedures in this study there are three stages, preparation stage, realization stage, and arrangement stage. This study was conducted in two test models. The results of this study indicate that before trialling the model by incorporating strategies Information Search by Talking Stick students who really have the interest to learn only 7 children (21.87%). After testing a model that is using model INSETA-STICK the model I test student interest increased to 14 children (43.75%) and the model II trials increased to 26 children (81.25%).